Sensitivity analysis and parameter selection of the modified Mohr–Coulomb model in foundation pit excavation in granite residual soil areas - Junfeng Shi; Zihang Yu; Weiping Jiang; Zhengjie Zhan; Pan Xia (Discover Applied Sciences)
Abstract In foundation pit excavation, granite residual soil is frequently used as a foundation-bearing layer, necessitating the consideration of its unique engineering characteristics in stability studies. Numerical analysis is a crucial method for evaluating the stability of excavation pits, with the Modified Mohr–Coulomb (MMC) model showing good applicability. However, research on the MMC model in granite residual soil regions remains limited. This study investigates the impact of key stiffness parameters ( $${E}_{ur}^{ref}$$ E ur ref , $${E}_{oed}^{ref}$$ E oed ref , and $${E}_{50}^{ref}$$ E 50 ref ) of the MMC model on the stability of excavation pit retaining structures, using case studies from the Zhuhai area. The research addresses the selection of stiffness parameters for different soil layers and proposes a proportional relationship between model stiffness parameters and field test mechanical parameters. Using the horizontal displacement of the underground diaphragm wall as an indicator, single-factor sensitivity analysis and orthogonal experimental methods were employed to determine the sensitivity and proportional relationships of stiffness parameters in the Zhuhai region. The findings indicate that $${E}_{ur}^{ref}$$ E ur ref has the most significant impact on model uncertainty, while $${E}_{50}^{ref}$$ E 50 ref has the least effect on horizontal displacement. The ratios of $${E}_{ur}^{ref}$$ E ur ref / $${E}_{50}^{ref}$$ E 50 ref , $${E}_{oed}^{ref}$$ E oed ref / $${E}_{50}^{ref}$$ E 50 ref , and $${E}_{50}^{ref}$$ E 50 ref to the deformation modulus ( $${E}_{0}$$ E 0 ) provide essential references for numerical simulation of excavation pits in the Zhuhai area.